A design of solar battery cleaning system by modularity method - Dien L.K. (EDP Sciences, 2021)
According to the World Bank statistical report, Vietnam has an average of 1,600-2,700 hours of sunshine and normal direct radiation averaging 4-5 kWh per square meter a day. Before 2017, solar energy was considered worthless in Vietnam's energy development strategy, but by the end of 2019, Vietnam overtook Malaysia and Thailand to become the country with the largest solar panel installation capacity in Southeast Asia. The photovoltaic projects in Vietnam has reached 5 gigawatts (GW), far exceeding from the target of 1 GW that proposed by the Government in 2020 [1]. The strong development of solar energy from industry to civil activities has led to the development of ancillary services such as installation, maintenance and commerce. To ensure the productivity, all solar panels must be cleaned to absorb solar energy as much as possible. In the paper, we mention on the design of a solar panel cleaning robot that has a compact size, easy to move through the panels, taking advantage of domestic factors to have an edge price. The highlight point in that work is our application of the modularity method to gain the best competition with the other existing products on the market.